2002
DOI: 10.1073/pnas.172403799
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of prions

Abstract: The ''protein only'' hypothesis states that the infectious agent causing transmissible spongiform encephalopathies is a conformational isomer of PrP, a host protein predominantly expressed in brain, and is strongly supported by many lines of evidence. Prion diseases are so far unique among conformational diseases in that they are transmissible, not only experimentally but also by natural routes, mainly by ingestion. A striking feature of prions is their extraordinary resistance to conventional sterilization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 86 publications
0
45
0
2
Order By: Relevance
“…C2 was also detected in glycosidase-treated brain extracts from Syrian hamsters infected with the Sc237 strain of prions. 2 The ϳ17-kDa PK-sensitive C-terminal PrP fragment, present in uninfected and RMLinfected mouse brain extracts (Fig. 2a), corresponds to the PrP C -specific cleavage product C1 fragment previously identified in human brain extracts (1).…”
Section: Prp C and Prp Sc Are Cleaved By Endogenous Proteases In Braimentioning
confidence: 55%
See 1 more Smart Citation
“…C2 was also detected in glycosidase-treated brain extracts from Syrian hamsters infected with the Sc237 strain of prions. 2 The ϳ17-kDa PK-sensitive C-terminal PrP fragment, present in uninfected and RMLinfected mouse brain extracts (Fig. 2a), corresponds to the PrP C -specific cleavage product C1 fragment previously identified in human brain extracts (1).…”
Section: Prp C and Prp Sc Are Cleaved By Endogenous Proteases In Braimentioning
confidence: 55%
“…During the disease process, PrP Sc acts as a template for conversion by imposing its conformation on the normally benign host-encoded version of the prion protein referred to as PrP C (reviewed in Ref. 2). The conversion of PrP C into PrP Sc involves a profound conformational change: PrP C has a high ␣-helical content and is virtually devoid of ␤-sheet while PrP Sc has high ␤-sheet content (3)(4)(5).…”
mentioning
confidence: 99%
“…In mammals, ''vegetative'' prion transmission by ingestion or infection has been observed to propagate prion diseases (35). In this study, we have demonstrated that, in the nonisogamously mating fungus P. anserina, prions of maternal origin are transmitted through a sexual pathway resulting in meiotic drive, with potential consequences for the level of prion infection in Podospora populations.…”
Section: Discussionmentioning
confidence: 73%
“…'' Considerable evidence supports a prion basis for the transmissible spongiform encephalopathies (TSEs) of mammals, with an amyloid form of the PrP protein as the culprit (1). The gene for PrP controls the clinical and pathological features of the TSEs (2-7).…”
mentioning
confidence: 99%